The Spread of Manufacturing to the Periphery 1870-2007: Eight Stylized Facts - Agustín S. Bénétrix; Kevin H. O'Rourke; Jeffrey G. Williamson (European Historical Economics Society (EHES), 2012)
This paper documents industrial output growth around the poor periphery (Latin America, the European periphery, the Middle East and North Africa, Asia, and sub-Saharan Africa) between 1870 and 2007. We provide answers to the following questions: When and where did rapid industrial growth begin in the periphery? When and where did peripheral growth rates exceed those in the industrial core? When was the high-point of peripheral industrial growth? When and where did it become widespread? When was the high-point of peripheral convergence on the core? How variable was the growth experience between countries? And how persistent was peripheral industrial growth?
Keywords: F1; N7; O2; 330